2022
DOI: 10.3390/antiox11101901
|View full text |Cite
|
Sign up to set email alerts
|

Interference Expression of StMSD Inhibited the Deposition of Suberin and Lignin at Wounds of Potato Tubers by Reducing the Production of H2O2

Abstract: Superoxide dismutase (SOD) actively participates in the wound stress of plants. However, whether StMSD mediates the generation of H2O2 and the deposition of suberin polyphenolic and lignin at potato tuber wounds is elusive. In this study, we developed the StMSD interference expression of potato plants and tubers by Agrobacterium tumefaciens-mediated transformation. The StSOD expression showed a marked downregulation in StMSD-interference tubers, especially StCSD2 and StCSD3. The content of O2•− exhibited a not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In addition, cinnamic acid was rapidly converted to trans-2-hydroxycinnamate under the catalysis of cinnamate 2-hydroxylase, followed by the generation of coumarine through the upregulation of β-glucosidase. Studies have shown that upregulation of PAL , C4H , and 4CL in plants can increase plant tolerance to biotic or abiotic stress [ 49 , 50 ]. Among them, overexpression of PAL has been proven to reduce the level of ROS in Arabidopsis seeds and leaves, increase the activity of POD, CAT, and the content of flavonoids, and reduce the accumulation of MDA [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cinnamic acid was rapidly converted to trans-2-hydroxycinnamate under the catalysis of cinnamate 2-hydroxylase, followed by the generation of coumarine through the upregulation of β-glucosidase. Studies have shown that upregulation of PAL , C4H , and 4CL in plants can increase plant tolerance to biotic or abiotic stress [ 49 , 50 ]. Among them, overexpression of PAL has been proven to reduce the level of ROS in Arabidopsis seeds and leaves, increase the activity of POD, CAT, and the content of flavonoids, and reduce the accumulation of MDA [ 51 ].…”
Section: Discussionmentioning
confidence: 99%